HUMAN VALUES AND RELIGIOUS FREEDOM. THE RIGHT OF LIFE IN THE REVELATION OF THE OBJECTION OF CONSCIENCE ACCORDING TO THE PERSPECTIVE OF SEVENTH-DAY ADVENTISM (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2023)
Human Values and Freedom of Religion. The Right to Life in The Revelation of The Objection of Conscience According to The Perspective of Seventh-day Adventism.Seventh-day Adventism suffered greatly from the two world wars, especially against the background of non-combat. Faith in God’s command not to kill has become the norm of life and the value of faith for conscientious objectors who have valued the Word more than they own life. In the course of history, Seventh-day Adventism experienced division, persecution, and suffering to the end, but with all these causes the Adventist message could not be overcome. Passing through different political systems, like a totalitarian monarchy, a Legionary government, and then a military one, the church fought back bravely by changing to fit the situation so that the standards of the Advent faith could be carried on. The values of Seventh-day Adventism embody human values and create the context for a peaceful and harmonious existence from the biblical point of view. This way arises the question: Can we still consider conscientious objection a human value from a theologian’s angle under the authority of God’s existence ?